Climate Change and Older Adults: Health Challenges and Practical Solutions in Healthcare - Klára (Magyar Gerontológia, 2025)
Climate change has emerged as a pressing public health concern worldwide, with its effects already visible across multiple sectors. As societies age, a growing number of older adults are becoming directly exposed to the adverse health consequences of climate-related events.